2013
DOI: 10.1128/aac.00734-13
|View full text |Cite
|
Sign up to set email alerts
|

A Cysteine Protease Inhibitor Rescues Mice from a Lethal Cryptosporidium parvum Infection

Abstract: h Cryptosporidiosis, caused by the protozoan parasite Cryptosporidium parvum, can stunt infant growth and can be lethal in immunocompromised individuals. The most widely used drugs for treating cryptosporidiosis are nitazoxanide and paromomycin, although both exhibit limited efficacy. To investigate an alternative approach to therapy, we demonstrate that the clan CA cysteine protease inhibitor N-methyl piperazine-Phe-homoPhe-vinylsulfone phenyl (K11777) inhibits C. parvum growth in mammalian cell lines in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 72 publications
1
54
0
3
Order By: Relevance
“…Cathepsins are cysteine proteases that are involved in the endosomal pathway and can be inhibited by cathepsin inhibitors such as K11777 (95) and its related vinyl sulfone analogs [149]. These compounds seem to be safe and effective against various parasitic infections in animal models and have broad-spectrum activities against enveloped RNA viruses such as CoVs (SARS-CoV, MERS-CoV, HCoV-229E, and HCoV-NL63), filoviruses (Ebola and Marburg viruses) and paramyxoviruses [149][150][151][152].…”
Section: Figure 13mentioning
confidence: 99%
“…Cathepsins are cysteine proteases that are involved in the endosomal pathway and can be inhibited by cathepsin inhibitors such as K11777 (95) and its related vinyl sulfone analogs [149]. These compounds seem to be safe and effective against various parasitic infections in animal models and have broad-spectrum activities against enveloped RNA viruses such as CoVs (SARS-CoV, MERS-CoV, HCoV-229E, and HCoV-NL63), filoviruses (Ebola and Marburg viruses) and paramyxoviruses [149][150][151][152].…”
Section: Figure 13mentioning
confidence: 99%
“…Nevertheless, research focused on anti-cryptosporidials continues to make substantial advancements. Several enzymes have been identified as potential drug targets, including calcium-dependent protein kinases [53], Clan CA cysteine proteases [55], IMPDH [57] and the folate biosynthesis pathway [56]. Other studies are testing compounds repurposed, which were developed for other indications.…”
Section: Discussionmentioning
confidence: 99%
“…Clan CA cysteine proteases are thought to be vital for host cell invasion and has been found to be structurally different than analogous enzymes in humans [54]. This protease can be inhibited utilizing N-methyl-piperazine-Phe-homoPhe-vinylsulfone phenyl (K11777) inhibits growth of Cryptospordium in vitro and has been shown to rescue immunocompromised mice from lethal infection [55]. …”
Section: The Way Forwardmentioning
confidence: 99%
“…Other drug targets include long‐chain fatty acyl‐coenzyme A synthetases (LC‐ACS), which are essential in fatty acid metabolism, and a recent study reported good efficacy of the ACS inhibitor triacsin C against cryptosporidial infection in mice . A parasite cysteine protease inhibitor was also effective in vitro and in an animal model . Other studies have focused on repurposing existing drugs to overcome the prohibitive costs of de novo drug development (estimated to be between $500 million and $2 billion per compound successfully brought to market) .…”
Section: Detection Diagnosis and Treatmentmentioning
confidence: 99%